Analisis Faktor-Faktor yang Menjelaskan Pengimplementasian Nilai-Nilai Utama (Corevalues) AKHLAK pada Karyawan di PT TASPEN (Persero) - Mohammad Zahran Pratomo; Yekti Widyaningsih; Dian Lestari (Jurnal Statistika dan Aplikasinya, 2023)
The development of the global economy is currently entering the era of Industry 4.0. Industry 4.0 cannot be faced only with technological development, but must involve social dynamics in it. Every company and agency must create a strategy in dealing with this era, including Badan Usaha Milik Negara (BUMN) by establishing main values that become the reference for the behavior of all human resources in BUMN. These core values consist of Trustworthy, Competent, Harmonious, Loyal, Adaptive, and Collaborative (AKHLAK). In practice, AKHLAK has not been implemented properly, even though the corevalues of AKHLAK need to be implemented by all human resources in BUMN. This study examines the significant factors explaining the implementation of AKHLAK core values on PT TASPEN (Persero) employees and to examine the profile of employees who have implementation core values high and low are based on significant factors. The factors used in this study are work motivation, work environment, employee welfare, socialization, employee commitment, religiosity, work stress, age, gender, education level, and years of service. The methods used in solving this research problem are the Partial Least Square (PLS) method and the Classification and Regression Tree (CART) method. The data used is primary data of 209 PT TASPEN (Persero) employees taken using purposive sampling. The results showed that work motivation, socialization, religiosity, and education level can significantly explain the implementation of AKHLAK. The profile of employees who have a high level of implementation of AKHLAK are employees with high level of religiosity, high work motivation, for all categories of educational levels, and work stress levels. The profile of employees who have a low level of implementation of AKHLAK are employees who have low religiosity and work motivation.